Research on presice point positioning and Real-Time Kinematics corrections for unmanned aerial vehicle global positioning systems. Issue 1 (2nd January 2017) - Ragauskas, Ugnius; Bručas, Domantas; Sužiedelytė Visockienė, Jūratė
Abstract: Unmanned Aerial Vehicles (UAVs) are used in different tasks with different flight path accuracy. To achieve a greater accuracy of flight trajectory GPS accuracy improvement methods are analyzed. The present article explains the main principles of GPS measurement. Precise Point Positioning (PPP) and Real-Time Kinematics (RTK) methods are described. and compared. Also, both methods have been tested.